The course of madness and changes in the care provided to patients in mental suffering - Millani, Helena de Fátima Bernardes; Valente, Maria Luisa L. de Castro (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2008)
This paper departs from new psychiatry concepts and practices crossing the context of collective mental health, considering the historical development that favors the understanding for the construction of new social and technical ways of dealing with madness, mental disease and human suffering. It also emphasizes that mental health care went through various changes, from institutionalization to Psychosocial Care Services, bringing about a change from the disease-cure to the existence-suffering paradigm.